Using storytelling to foster the teaching and learning of gravitational waves physics at high-school - Tuveri, M; Steri, A; Fadda, D (Physics education, 2024)
Studies in Physics Education Research show that interdisciplinary approaches in education foster students’ motivation, creativity, curiosity, and interest in physics. We discuss their features and potential role in bringing contemporary physics topics to high school and how to use them to integrate formal educational programs. We make an explicit example of the use of storytelling and theatrical techniques to introduce secondary school students to black holes and gravitational wave topics. The Educational Division of the Physics Department at the University of Cagliari designed the activity. Participants were 200 high-school students (17 to 19 years old) from five schools (scientific, humanities) in Sardinia. Through a research questionnaire, we measure the efficacy of using artistic tools to communicate and teach the proposed subjects. We collected 76 answers. Results show that our methodology helps introduce students to contemporary physics themes, fostering their interest and learning of such content. Students from the humanities significantly appreciated the use of poetry and artistic tools more than their scientific peers. Finally, we discuss the potentiality of our approach in orientating students towards a STEAM (STEM and Arts) career.